THE EFFECT OF”THE ASSOCIATED GOA FORMOL VACCINE AGAINST COLIBACTERIOSIS AND SALMONELLOSIS OF CALF, LAMB AND PIG CHILDREN " ON THE BODY OF LAMBS (Neo Scientific Peer Reviewed Journal, 2024)
In the article, as a result of vaccination of lambs with the vaccine “GOA-associated formol vaccine against colibacillosis and salmonellosis of calves, lambs and piglets”, the duration of immunity was established in experiments at 9-12 months. In the treatment of colibacillosis and salmonellosis in lambs, it was noted that due to the stabilization of the immune system due to gamma globulins in hyper immune blood serum, the effectiveness exceeds 90 percent. The article also provides information about hematological and biochemical changes in the blood of lambs with a mixed form of these diseases and the sensitivity of E.coli and salmonella to antibiotics.